Analisa Hubungan antara Size, Market Position dan Product Life Cycle dengan Penggunaan Balanced Scorecard pada Sektor Rumah Sakit di Surabaya - Yuliana, Yuliana (Business Accounting Review, 2013)
The research conducted to know the relationship among market position, organization size and product life cycle and the use of balance scorecard in hospital sector in Surabaya. Because of the changing business environement, hospital must create more benefit. As an example, hospital used balance scorecard to measure performance. The research used 34 hospital which was general hospital, spesialized hospital, and clinic or polyclinic. Data analysis technique used was the correlation test to know whether there was a relationship. The result of this study shown that there was a significant relationship among the market position, organization size, and product life cycle and the use of balance scorecard. And the result of this study was the most highest perspective were on customer perspective (4,26), internal business proses perspective (4,26), financial perspective (3,95) and learning and growth perspective (3,87)